Modification of Kaolin with Carbon Quantum Dots as Composite for Methylene Blue Removal: Literature Review and Experiment - Nonni Soraya Sambudi; Yuvan Sithambaran; Khee Chung Hui; Muhammad Wahyu Nugraha; Norashikin Ahmad Kamal; Noorfidza Yub Harun; Suriati Sufian (Indonesian Journal of Science and Technology, 2022)
The modification of kaolin with nano-size fillers has exhibited excellent performance in the adsorption process. Carbon quantum dots (CQDs) are the new generation of nanoparticles that have attracted interest for their utilization as modifiers. In this study, a composite of metakaolin(MK)/CQDs was synthesized and tested for methylene blue (MB) removal. The heating and acid-alkali treatment of kaolin transformed it into MK. The interaction between MK and CQDs was analyzed using XPS to detect the binding of pyridic NH2 and C-N. By loading CQDs into the kaolin matrix, the surface area was improved and the removal of MB increased. For a lower MB concentration at 5 ppm, the removal efficiency could reach 96%. The composite exhibited good regeneration through the recyclability test.